Relationship between Serum Vascular Endothelial Growth Factor Levels and Stages of Diabetic Retinopathy and Other Biomarkers - Nakhleh E. Abu-Yaghi; Nafez M. Abu Tarboush; Ala M. Abojaradeh; Amal S. Al-Akily; Esra’a M. Abdo; Laith O. Emoush (Journal of Ophthalmology)
Aim. This study aims to measure serum vascular endothelial growth factor (VEGF) levels in a sample of Jordanian patients and to determine their relationship with the different stages of diabetic retinopathy. It also explores the correlation between VEGF concentrations and different biochemical and demographic findings. Materials and Methods. A total of 167 adults participated in the study. Participants were divided into two main categories: patients with diabetes mellitus (DM) type 2 without diabetic retinopathy (DR) (N = 62) and patients with DM type 2 affected by DR (N = 105). DR patients were further subclassified into nonproliferative (N = 41) and proliferative (N = 64). Basic laboratory tests were measured to correlate with VEGF levels. Irisin, a hormone linked to diabetic retinopathy was also measured and correlated with VEGF. Results. Serum VEGF was found to positively correlate with the severity of diabetic retinopathy. The means of VEGF serum concentrations were 60 pg/mL for controls, 133 pg/mL for nonproliferative DR patients, and 229 pg/mL for proliferative DR patients. We found a significant positive correlation with glycosylated hemoglobin (HbA1c), and a significant negative correlation with high-density lipoprotein (HDL) levels, age, and irisin. Conclusion. In this cohort of Jordanian diabetics, serum VEGF concentrations strongly correlated with the presence and stages of diabetic retinopathy, suggesting it as an appropriate indicator for diabetic retinopathy early detection and management in this society. VEGF levels also significantly correlated with HbA1c, HDL, and irisin levels. Further studies are encouraged to explore these relationships in other ethnic groups and with different diabetic complications.